Frangulin B, an Antagonist of Collagen-Induced Platelet Aggregation and Adhesion, Isolated from Rhamnus formosana - Teng, Che-Ming; Lin, Chien-Huang; Lin, Chun-Nan; Chung, Mei-lng; Huang, Tur-Fu (Thrombosis and Haemostasis, 1993)
Emodin and its glycoside frangulin B were isolated from the plant Rhamnus formosana. Emodin inhibited the aggregation of rabbit platelets induced by arachidonic acid and collagen, without affecting that by ADP or PAF, while emodin acetate had no any antiplatelet effect. Frangulin B inhibited selectively and concentration-dependently collagen-induced aggregation and ATP release in rabbit platelets, without affecting those induced by arachidonic acid, ADP, PAF and thrombin. Frangulin B also inhibited the platelet aggregation induced by trimucytin which was reported to be a collagen receptor agonist isolated from Trimeresurus muscrosquamatus snake venom. The aggregability of platelets inhibited by frangulin B could be recovered after washing the platelets. Frangulin B also selectively suppressed the thromboxane B2 formation caused by collagen, but not those by arachidonic acid and thrombin. Similarly, the formation of inositol phosphate caused by collagen was also suppressed by frangulin B, while that of PAF or thrombin was not affected. In the presence of PGE1, frangulin B also decreased Mg2+-dependent platelet adhesion to collagen. It is concluded that frangulin B may be an antagonist of collagen receptor in platelet membrane.